Leaching of Chalcopyrite Ore Agglomerated with High Chloride Concentration and High Curing Periods - Velasquez-Yevenes, L (Elsevier B.V., 2018)
It is well known that the leaching of chalcopyrite has very slow kinetics. The generally higher reactivity of chalcopyrite in chloride as opposed to sulfate solutions has resulted in many studies of chloride systems for the hydrometallurgical treatment of chalcopyrite. Despite much progress on the chloride leaching process, agglomeration and curing has received less attention over the past years. This paper reports a study on the effect of addition of chloride ion in the agglomeration and the effect of curing time on the overall leaching process of chalcopyrite ore. The work involved leaching tests carried out in columns containing 3.0 kg of agglomerated ore irrigated with raffinate solution under ambient conditions. Experiments with agglomerates produced at different concentration of chloride (20, 50 and 70 kg/t) leach at approximately the same rate. It has been demonstrated that chloride ions presence is necessary to improve the leaching kinetics, but high concentrations of chloride are not essential under ambient conditions. The rate of dissolution of chalcopyrite ore agglomerated with high concentrations of acid and chloride ions increases as the curing period increases from 15 to 80 days observing extraction of copper up to 60% in 20 days of leaching. In all experiments, the shape of the leach curves indicate that the copper that has been solubilized during the curing period is rapidly leached followed by continuous slow leaching thereafter. This study supports the addition of chloride at the agglomeration stage as a viable route for the treatment of low-grade copper sulfide ore. © 2018